The NPA Menace: A Study of Non-Performing Assets in India's Co-Operative Banks - Abhijith Sankar; Natarajamurthy P (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
The prevalence of Non-performing Assets has been a persistent problem faced by the Indian banking sector in general and the Indian co-operative banking sector in particular. In this context, the present study undertakes a descriptive and trend-based empirical examination of NPA patterns among the various types of urban and rural co-operative banks in the country over the period of more than two and a half decades (1996-97 to 2022-23). This study conducted a descriptive, trend-based, and CAGR-based examination of the Gross Non-performing Assets of the various segments of India’s co-operative banking sector. The study finds a bifurcation in Gross NPA ratios across the co-operative sector during this period: Urban Co-operative banks and the short-term rural credit structure (StCBs and DCCBs) showed sustained improvement in asset quality, whereas the long-term rural cooperative credit structure (SCARDBs and PCARDBs) recorded deterioration. These findings imply that policy attention has been concentrated on the urban cooperative segment, while the long-term rural credit structure, despite a greater need for intervention, has received less sustained reform focus. A comprehensive strategy across the cooperative credit structure is imperative to ensure India's cooperative banking sector's long-term sustainability and credit access for underserved populations.